15th Internationanternational Congress of Speleology: Are you Ready to Register?! - Veni, G.; Eavis, A. (Спелеологія і карстологія, 2008)
The International Congress of Speleology (ICS) is the world’s premier speleological event. An event of the International Union of Speleology (UIS), it is held once every four years in a location selected by the delegates of the UIS member nations. The next ICS will be held in Kerrville, Texas, USA on 19-26 July 2009.